The Inequity of Women in Art History: New Structures for a Changed World in Adult Education - Joan Hastings (Adult Education Research Conference, 2013)
This study examines the social, economic, political, religious, and cultural climate of gender inequity in art history. The outcome of the study is intended to ultimately create a more inclusive contemporary art history course for adult learners. It is important to adult education because it supports the individual along with other benefits to both the learner and the facilitator. The body of research and its findings within this study will be of interest to adult educators, art historians, women studies professionals and students.